2015
DOI: 10.1007/s10620-015-3728-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Nonalcoholic Fatty Liver Disease and Economy

Abstract: This study suggested that countries with higher economic status tend to present a higher prevalence of NAFLD. It is believed to provide a distinctive epidemiologic perspective to global situation of NAFLD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
67
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(73 citation statements)
references
References 43 publications
5
67
0
1
Order By: Relevance
“…There were three differences between two studies. Firstly, the prevalence of NAFLD in our study was 20.5% that was close to the average level based on a number of population-based surveys [15], while the study of Li et al reported a prevalence of 37.0%. We believe our study could present a current situation of NALFD in western China.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…There were three differences between two studies. Firstly, the prevalence of NAFLD in our study was 20.5% that was close to the average level based on a number of population-based surveys [15], while the study of Li et al reported a prevalence of 37.0%. We believe our study could present a current situation of NALFD in western China.…”
Section: Discussionsupporting
confidence: 83%
“…NAFLD has become an emerging public health concern, given its remarkable growth in the worldwide over the recent decades [15]. Specifically, due to the westerni- zation of lifestyle and the aging population, the prevalence of NAFLD, closely related with metabolic disorders such as central obesity, hypertriglyceridemia and insulin resistance, has witnessed a rapid increase in Asia [16,17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonalcoholic fatty liver disease (NAFLD) is the most frequent chronic liver disease in developed countries and its increased prevalence parallels the rise in obesity, type 2 diabetes and metabolic syndrome in recent decades (Tuyama & Chang 2012, Yki-Jarvinen 2016. NAFLD encompasses hepatic steatosis driven by factors other than excessive alcohol consumption and is estimated to affect 25% of the global population (Zhu et al 2015). While NAFLD most commonly refers to fatty liver resulting from overnutrition and consumption of a western diet, NAFLD may also be induced by endocrine disorders, viral infections or side effects of pharmacological therapies.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of obesity-related metabolic disorders is mounting to epidemic proportions in the world (1)(2)(3). Obesity, insulin resistance (IR), dyslipidemia, hyperglycemia, and hypertension are frequently coincident in one individual, in a disorder defined as metabolic syndrome (MetS) (4).…”
Section: Introductionmentioning
confidence: 99%